2019
DOI: 10.3390/cancers11111743
|View full text |Cite
|
Sign up to set email alerts
|

WEE1 Inhibition Enhances Anti-Apoptotic Dependency as a Result of Premature Mitotic Entry and DNA Damage

Abstract: Genomically unstable cancers are dependent on specific cell cycle checkpoints to maintain viability and prevent apoptosis. The cell cycle checkpoint protein WEE1 is highly expressed in genomically unstable cancers, including diffuse large B-cell lymphoma (DLBCL). Although WEE1 inhibition effectively induces apoptosis in cancer cells, the effect of WEE1 inhibition on anti-apoptotic dependency is not well understood. We show that inhibition of WEE1 by AZD1775 induces DNA damage and pre-mitotic entry in DLBCL, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Furthermore, there is an unmet need to translate theoretical information into clinical practice which has been done, for example, with the use of adavosertib, an WEE1 inhibitor, to increase response in DLBCL patients. In line with this, the incorporation of single-cell sequencing technology can help identify B-cell stages (dark/light zone) and cell cycle phases to further amplify the possibilities for therapy options [ 17 , 46 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is an unmet need to translate theoretical information into clinical practice which has been done, for example, with the use of adavosertib, an WEE1 inhibitor, to increase response in DLBCL patients. In line with this, the incorporation of single-cell sequencing technology can help identify B-cell stages (dark/light zone) and cell cycle phases to further amplify the possibilities for therapy options [ 17 , 46 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…They further evaluated these targets using inhibiting drugs (AZD1775 for WEE1 and olaparib for PARP1) on different cell lines finding increased cytotoxic effects. Furthermore, a later study from the same group led to the discovery that combined WEE1 and anti-apoptotic protein inhibition enhances premature mitotic entry and DNA damage which may benefit genomic unstable DLBCL cells [ 17 , 46 ]. Moreover, there are over 20 clinical trials exploring adavosertib, the most potent and selective WEE1 inhibitor, as a single agent or in combination for different indications ( , October 2020).…”
Section: Gwas In B-cell Nhlmentioning
confidence: 99%
“…Moreover, strong synergism has been observed by combining adavosertib with small molecules, including DDR-related inhibitors (CDK2 [ 89 ], CDK4-6 [ 149 ], CHK1 [ 103 , 140 142 ], ATM [ 132 135 ], AURORA A [ 147 ], PARP1 [ 144 ], SIRT1 [ 148 ] inhibitors), histone deacetylase (HDAC) inhibitors [ 41 , 130 , 131 ], tyrosine kinase inhibitors (BCR-ABL1 inhibitors [ 35 ]), anti-apoptotic protein inhibitors (BCL2 and MCL1 inhibitors [ 143 ]), mTOR inhibitor [ 136 139 ], and proteasome inhibitors [ 36 ].…”
Section: Development Of Wee1 and Pkmyt1 Inhibitorsmentioning
confidence: 99%
“…Preclinical evidence has indicated that Wee1 inhibitors show synergistic effects when combined with histone deacetylase (HDAC) inhibitors [ 49 ], proteasome inhibitors [ 50 ], tyrosine kinase inhibitors [ 51 ], anti-apoptotic protein inhibitors (enhance dependency on BCL-2 and/or MCL-1 inhibition) [ 52 ], and mammalian (or mechanic) target of rapamycin (mTOR) inhibitors [ 53 ]. This latter study is particularly noteworthy for PCa as mTOR inhibition was found to synergize with Wee1 inhibition in KRAS mutant tumors.…”
Section: Targeting Dna Repairing Deficiency and Microsatellite Insmentioning
confidence: 99%